2022
DOI: 10.5435/jaaosglobal-d-22-00035
|View full text |Cite
|
Sign up to set email alerts
|

Jump in Elective Total Hip and Knee Arthroplasty Numbers at Age 65 Years: Evidence for Moral Hazard?

Abstract: Introduction:Total knee arthroplasty (TKA) and total hip arthroplasty (THA) are outstanding options for many older patients at the discretion of the patient and the surgeon. As patients turn 65 years, greater than 98% of the US population becomes eligible for Medicare, and this represents a time of changing healthcare coverage for many.Methods:Patients undergoing elective TKA and THA were abstracted from the 2012 to 2018 National Surgical Quality Improvement Program database. Incidences of TKA and THA (combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…the incidence was slightly higher in patients > 70 years (1.90%) than in patients < 70 years (1.68%). The majority of patients requiring arthroplasty are > 50 years of age [ 36 , 37 ]. Patients in this age group tend to have underlying diseases and a weaker immune system than younger patients, and the probability of infection may be higher in older patients than in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…the incidence was slightly higher in patients > 70 years (1.90%) than in patients < 70 years (1.68%). The majority of patients requiring arthroplasty are > 50 years of age [ 36 , 37 ]. Patients in this age group tend to have underlying diseases and a weaker immune system than younger patients, and the probability of infection may be higher in older patients than in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is a successful and effective treatment in pain relief and functional restoration for various hip diseases, and it might constitute financial burden for the healthcare system [1]. Cases of elective THA might increase over the next decade as the elderly population grows and the impact from COVID-19 pandemic on the elective surgical operations lessens [2,3]. Previous literature suggested that a substantial rise of THA should be addressed in health policies, and the diagnosis-related groups (DRGs) payment had potential cost-saving implications with possible higher efficacy and better use of the medical insurance [4,5].…”
Section: Introductionmentioning
confidence: 99%